MicroRNA-30a-5p promotes differentiation in neonatal mouse spermatogonial stem cells (SSCs) - Maryam Khanehzad; Seyed Mehdi Nourashrafeddin; Farid Abolhassani; Shokoofeh Kazemzadeh; Soheila Madadi; Elham Shiri; Parastoo Khanlari; Zahra Khosravizadeh; Azim Hedayatpour (BMC, 2021)
Abstract Background The importance of spermatogonial stem cells (SSCs) in spermatogenesis is crucial and intrinsic factors and extrinsic signals mediate fate decisions of SSCs. Among endogenous regulators, microRNAs (miRNAs) play critical role in spermatogenesis. However, the mechanisms which individual miRNAs regulate self- renewal and differentiation of SSCs are unknown. The aim of this study was to investigate effects of miRNA-30a-5p inhibitor on fate determinations of SSCs. Methods SSCs were isolated from testes of neonate mice (3-6 days old) and their purities were performed by flow cytometry with ID4 and Thy1 markers. Cultured cells were transfected with miRNA- 30a-5p inhibitor. Evaluation of the proliferation (GFRA1, PLZF and ID4) and differentiation (C-Kit & STRA8) markers of SSCs were accomplished by immunocytochemistry and western blot 48 h after transfection. Results Based on the results of flow cytometry with ID4 and Thy1 markers, percentage of purity of SSCs was about 84.3 and 97.4 % respectively. It was found that expression of differentiation markers after transfection was significantly higher in miRNA-30a- 5p inhibitor group compared to other groups. The results of proliferation markers evaluation also showed decrease of GFRA1, PLZF and ID4 protein in SSCs transfected with miRNA-30a-5p inhibitor compared to the other groups. Conclusions It can be concluded that inhibition of miRNA-30a-5p by overexpression of differentiation markers promotes differentiation of Spermatogonial Stem Cells.